Analisis Minat Beli: Dampak Dari Pengetahuan Produk Edible Flower (Studi Kasus Pada Restoran- Restoran di Kota bandung) - Sri Marini (Tourism Scientific Journal, 2020)
The development of the tourism and hospitality industry has encouraged the food industry to use edible flowers as an appetizing dish. The growth of gastronomy should stimulate its use to increase the value of local products, lifestyle, culture and even nutrition. Edible flowers, which are currently only used for garnishes, can actually be consumed. Hotels, restaurants, cake and pastry entrepreneurs have started using edible flowers as raw material for production. Apart from providing aesthetic value, flowers can create unique flavors to food. Purchase intention is influenced by product knowledge. Low product knowledge can lead to low purchase intention. This study aims to determine product knowledge, the purchase intention and the effect of product knowledge on purchase intention of edible flower restaurants in the city of Bandung. The method used in this research is descriptive and verification research methods. In this study, the population is the restaurants in the city of Bandung. Technique sampling used in this study is proportional random sampling technique. To test the research hypothesis, a simple linear regression analysis using SPSS was used. The results showed that the product knowledge of edible flower in restaurants at Bandung in the average category. Likewise, the purchase intention of edible flower restaurants in the city of Bandung is in the sufficient category too. The result of the regression analysis shows that product knowledge has a significant effect on the purchase intention of edible flower restaurants in the city of Bandung. The determinant coefficient value of 0.828 shows that the effect of product knowledge on purchase intention edible flower restaurants in Bandung is 82.8% and the remaining 17.2% is influenced by other factors not examined in this study.